Сучасний стан та напрями розвитку наукового обґрунтування оперативно-розшукового забезпечення судового провадження - Антонов, Костянтин Володимирович; Антонов, Константин Владимирович; Antonov, Konstantin; Савенко, С. А.; Savenko, S. (Одеса : Юрид. л-ра, 2012)
In this article scientific reserches of operative and investigative ensuring of criminal proceedings were analyzed. In particular, were reviewed main directions of scientific researches in the theoretical aspects of operative and investigative activity, criminal process and administrative law. Was substantiated that scientific researches of this problem are in the process of metodological ackground developement.
Антонов К. В. Сучасний стан та напрями розвитку наукового обґрунтування оперативно-розшукового забезпечення судового провадження / К. В. Антонов, С. А. Савенко // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 698-706.
Keywords: наукове забезпечення; оперативно-розшукова діяльність; кримінальне провадження; судове провадження; научное обеспечение; оперативно-розыскная деятельность; уголовное производство; судебное производство; Scintific ensuring; operative and investigative activity; criminal proceedings; judicial proceedings